Konseling sebagai Upaya Meningkatkan Kepemimpinan Transformasional - Nur Pratiwi Noviati; Sri Hartati (Universitas Islam Indonesia, 2009)
This research is aimed to analyze the effectiveness of counseling as an effort to improve transformational leadership in managing organizational change. The research subject were 4 individuals whose transformational leadership style may be improved. Research subject was selected randomly from 7 heads of division In FTI Ull. Selected subjects were divided Into 2 groups (2 subjects in experiment group, and 2 sub/eots in control group). Experiment group was provided with counseling treatment directed to be able to understand transformational leadership concept and applying it in working site applying Measurement was done before treatment using 33 statements on transformational leadership from Multifaclor Leadership Questionnaire (MLQ) and 2 months after treatment using MLQ and transformational behaviour checklist. The data obtained was compared and analyzed using Chi-Square test Inaddkion. the result of counseling and working sheet were denned from implementation andarÃ© also used in measuring effectiveness of counseling Qualitative analysis was stressed in this research. The result of the research indicated that counseling can improve individual transformational leadership.Keywords. Transformational, Leadership, Counseling